Taḥlīlu Ṭuruqi al Tarjamati fī Kitābi Fatḥil Qarībi li al Syaikh Syamsi al Dīni Abū ‘Abdillah (Dirāsatun fī ‘Ilmi al Tarjamati) - Kholik, Idham; Daud, Izzat Muhammad (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
The author discusses the translation method used in the Fathul Qorib translation book. The formulation of the problem is: 1. What are the translation methods used in the Fathul Qorib translation book? 2. What method is suitable for translating the book of fathul qorib? The purpose of this study is to describe and find out: 1. What translation is used by the translator in the book of Fathul Qorib. 2. What kind of translation is suitable for translating the book of Fathul Qorib. The method used in this research is a qualitative descriptive literature research. And the technique used is by reading, writing and studying as well as analyzing the data with documentation. It can be concluded from the results of this study, namely: the translation used in translating the book of fathul qorib is a literal translation of 3 sentences, a faithful translation of 91 sentences and a free translation of 38 and the translation that is suitable to be used in translating this Fathul Qorib book is the Faithful Translation. With the description of Setia's translation, that is the translation that is focused on the intent of the original translation so that it is right on target and easy to understand.